Metacognitive Monitoring of the Solution of Tasks for Examination: Psychological Predictors and Relations with the Academic Success - Fomin A.E. (Психолого-педагогические исследования)
The role of researches of metacognitive monitoring of knowledge in achievement of metasubject educational results is opened. The concept "metacognitive monitoring", its role of the academic success and theoretical approaches to an explanation of distortions of a self-assessment are analysed by pupils of own knowledge. In an empirical part on material of a research of students of average and professional educational institutions (N = 72; average age of 15,5 years; 45 young men, 27 girls) are shown: a) according to the ANOVA the accuracy of judgments of monitoring acts as a progress factor on discipline «English» (p=0,002); b) a significant psychological predictor of monitoring is the subjective availability of the answer to questions of test tasks acting as the basis for formulation of metacognitive judgments (р =0,000). In the conclusion the value of results of a research for practice of formation of reflexive competences of structure of metasubject results of training is discussed.